Perbandingan Efikasi Insektisida Rumah Tangga Oil Liquid terhadap Pengendalian Nyamuk Aedes aegypti dengan Metode Glass Chamber - Imam Suhada; Retno Hestiningsih; Martini Martini; Susiana Purwintasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
High dengue cases in Indonesia to encourage the public to control the dengue vector. One vector control using insecticides liquid oil. More and more household insecticides used by the community lead to resistance in mosquitoes. The purpose of this study was to measure the effectiveness of insecticides X, Y, Z on the control of Aedes aegypti mosquitos. Testing the power to kill 3 household insecticide products that contain active insecticide transflutrin 1.436 X, Y insecticide active ingredient praletrin 0.572 g / l, d alletrin 3.245 g / l, cyfluthrin 0.286 g / l, Z insecticide active ingredient Sipermetrin 1.00 g / l , imiprotin 0.50 g / l, praletrin 0.50 g / l. This research was conducted by entering the 20 mosquitoes in a glass chamber and then exposed to the insecticide and the observed number of mosquitoes that pass out with the time interval from 0.5 to 20 minutes. Anova test analysis results can be seen no difference in the number of mosquitoes that die with 3 insecticide. Knock-down time 50 (KT50) and KT90 fastest is insecticide X with 97.842 seconds, while for the Aedes aegypti mosquito KT90 took 516.366 seconds. Research must be done on a regular basis on the effective use of household insecticides and monitoring products on the market to avoid insecticide resistance